Gliogenesis from the subventricular zone modulates the extracellular matrix at the glial scar after brain ischemia - Ardaya, Maria; Tiveron, Marie-Catherine; Cremer, Harold; Rubio-López, Esther; Martín, Abraham; Dehay, Benjamin; Pérez-Cerdá, Fernando; Matute, Carlos; Soria, Federico N; Cavaliere, Fabio (eLife, 2025)
Activation of the subventricular zone (SVZ) following cerebral ischemia is one of the brain’s early responses to counteract neuron loss and minimize tissue damage. Impaired brain regions communicate with the SVZ through various chemotactic signals that promote cell migration and differentiation, primarily involving neural stem cells, neuroblasts, or glioblasts. However, the activation of gliogenesis and the role of newly formed astrocytes in the post-ischemic scenario remain subjects of debate. We have previously demonstrated that adenosine release after brain ischemia prompts the SVZ to generate new astrocytes. Here, we used transient brain ischemia in mice to identify the cellular origin of these astrocytes within the SVZ neurogenic niche and investigate their role in the pathological process. By combining immunofluorescence, BrdU-tracing, and genetic cell labeling, we tracked the migration of newborn astrocytes, positive for the proteoglycan marker Thbs4, from the dorsal and medial SVZ to the perilesional barrier surrounding the ischemic core, known as the ‘glial scar’. We found that these Thbs4-positive astrocytes modulate the dense extracellular matrix at the lesion border by both synthesizing and degrading hyaluronan. We also show that while the accumulation of hyaluronan at the lesion site is sufficient to recruit newborn astrocytes, its degradation at the SVZ correlates with gliogenesis. These findings suggest that newborn astrocytes could be a promising pharmacological target for modulating the glial scar after brain ischemia and facilitating tissue regeneration.